ANALYSIS OF EDUCATION VALUE OF CHARACTER IN NOVEL 5 CM BY DONNY DHIRGANTORO - Rut Leni Natalia Sembiring; Emma Martina Br pakpahan (IKIP Siliwangi, 2021)
Character education is closely related to moral education, which is to shape and train individual abilities continuously for self-improvement towards a better life. Novel is a literary work that can convey the values of character education. The research aims to analyzing the values of character education in the novel 5 cm by Donny dhirgantoro. This research is a qualitative study using a descriptive design method. the data analysis technique by reading the entire data, analyzing the data in more detail and restating the data by described and interpreting the data. The result of this study are the value of character education contained in the novel “ 5 cm” by Donny Dhirgantoro, namely, religious, hard work, love to read, friendly and communicative, social care, and love the homeland.